The study of Influencing Maintenance Factors on Failures of Two gypsum Kilns by Failure Modes and Effects Analysis (FMEA) - Iraj Alimohammadi; Dr.Javad Adl (Iranian Journal of Health, Safety and Environment, 2014)
Developing technology and using equipment in Iranian industries caused that maintenance system would be more important to use. Using proper management techniques not only increase the performance of production system but also reduce the failures and costs. The aim of this study was to determine the quality of maintenance system and the effects of its components on failures of kilns in two gypsum production companies using Failure Modes and Effects Analysis (FMEA). Furthermore the costs of failures were studied. After the study of gypsum production steps in the factories, FMEA was conducted by the determination of analysis insight, information gathering, making list of kilns' component and filling up the FMEA's tables. The effects of failures on production, how to fail, failure rate, failure severity, and control measures were studied. The evaluation of maintenance system was studied by a check list including questions related to system components. The costs of failures were determined by refer in accounting notebooks and interview with the head of accounting department. It was found the total qualities of maintenance system in NO.1 was more than NO.2 but because of lower quality of NO.1's kiln design, number of failures and their costs were more. In addition it was determined that repair costs in NO.2's kiln were about one third of NO.1's. The low severity failures caused the most costs in comparison to the moderate and low ones. The technical characteristics of kilns were appeared to be the most important factors in reducing of failures and costs.